Modified infra orbital approach for maxillary nerve block in dogs for rhinoscopic procedures - Vijayakumar, G; Annie Mariam John; Mohamed Shafiuzama; S.Kavitha (Indian Journal of Veterinary Medicine, 2024)
A trial had been conducted to assess the efficacy of modified infra orbital approach for maxillary block over infra orbital block for rhinoscopic procedures in dogs with nasal cavity disease. The dogs were subjected to clinical, haemato-biochemical and radiographic examination. Six dogs with nasal cavity disease were subjected to rhinoscopy. These dogs were fasted for 12 hours before anaesthetic induction. An indwelling intravenous catheter was placed. A cuffed endotracheal tube was placed and the cuff was inflated. The animals were administered with glycopyrrolate (@ 0.01-0.02 mg/kg SC / IM). Premedication with butorphanol (@ 0.2 – 0.4 mg/kg IM) and xylazine (@ 0.2 – 1.1 mg/kg IM) and induction of anaesthesia by propofol (@ 1-2 mg/kg IV) were done. Maintenance of anaethesia was carried out with ketamine (@ 5 mg/kg IV) and diazepam (@ 0.25 mg/kg IV) combination. Monitoring of electrocardiogram, blood pressure and oxygen saturation were done as per standard techniques. Monitoring of electrocardiogram, blood pressure and oxygen saturation were done as per standard techniques. Local infiltration with 2% lignocaine was done using infra- orbital approach on one side while modified infra- orbital method for maxillary block was used on other side of the dog. Rhinoscopy was carried out using anterior and posterior approach. The efficacy of technique was assessed based on response of the dog for irrigation used during rhinoscopy, biopsy and swab procedures. The results of the study indicated that modified infra orbital approach for maxillary nerve block suppressed the sneeze and other reflexes when compared infra orbital nerve block during rhinoscopy in dogs.